2020
DOI: 10.3390/jcm9041090
|View full text |Cite
|
Sign up to set email alerts
|

Association of HSV-1 and Reduced Oral Bacteriota Diversity with Chemotherapy-Induced Oral Mucositis in Patients Undergoing Autologous Hematopoietic Stem Cell Transplantation

Abstract: Oral mucositis (OM) is a common complication of chemotherapy and remains a significant unmet need. The aim of this study was to investigate the role of oral bacteriota and HSV-1 in OM. Forty-six patients admitted for autologous hematopoietic stem cell transplantation were longitudinally evaluated for OM, Candida, HSV-1, and leukocyte count, and buccal mucosal bacterial samples were obtained during their admission period. The bacterial communities collected at the baseline and post-chemotherapy, chosen from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…The overall diversity of the oral microbiota decreased after chemotherapy, and the bacterial composition changed after the start of chemotherapy. A decrease in the diversity of the oral microbiota due to chemotherapy for hematopoietic malignancies has been reported in children with leukemia [20] and in patients undergoing autologous hematopoietic stem cell transplantation [21], which is consistent with the results of our study. Furthermore, recent reports have shown that changes in the diversity of not only the gut microbiota [22], but also the oral microbiota, during chemotherapy for leukemia are associated with the risk of infection during treatment [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…The overall diversity of the oral microbiota decreased after chemotherapy, and the bacterial composition changed after the start of chemotherapy. A decrease in the diversity of the oral microbiota due to chemotherapy for hematopoietic malignancies has been reported in children with leukemia [20] and in patients undergoing autologous hematopoietic stem cell transplantation [21], which is consistent with the results of our study. Furthermore, recent reports have shown that changes in the diversity of not only the gut microbiota [22], but also the oral microbiota, during chemotherapy for leukemia are associated with the risk of infection during treatment [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there was no association between oral shedding of herpesviruses and type of HSCT (allogeneic versus autologous). However, the severity of OM was associated with HSV‐1 reactivation and decrease in oral bacterial diversity (Lee et al., 2020), showing the influence of the imbalance on the local microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus type-1 (HSV-1) is a virus transferred usually by oral-to-oral contact, while HSV-2 is transferred mainly sexually. In the study of Lee, chemotherapy was associated with reduced diversity of oral bacterial microbiota and increased occurrence of HSV-1 infection in patients undergoing auto-HSCT [4]. Interestingly, HSV-1 infection reduced microbial diversity after treatment with chemotherapy.…”
Section: Herpesviridae (Hsv)mentioning
confidence: 97%
“…Nowadays, due to widespread different environmental factors, inadequate foods, use of antimicrobial drugs influencing the microbiome, the bacterial community can be disrupted [2,3]. Human microbiota colonizing the oral mucosa, intestinal tract, genital tract, and airways plays an important role in the human body and influences the development of chronic diseases such as alcoholic liver disease, autoimmune liver disease, or cancers [2,4,5]. It has been evidenced that the intestinal microbiome can be involved in inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), type 2 diabetes (D2M), and colorectal cancer [2,6].…”
Section: Introduction and Purposementioning
confidence: 99%